10000 years cement – Can hydrated cement last as much as long-lived radionuclides?. (October 2019) - Ferreira, Eduardo G.A.; Marumo, Júlio T.; Franco, Margareth K.K.D.; Yokaichiya, Fabiano; Vicente, Roberto
Abstract: This review is focused on the long-term performance of cementitious materials in a repository for radioactive waste. During the last few years, the disposal of disused sealed radioactive sources (DSRS) in a borehole type repository has been studied by many countries. The borehole concept is particularly useful to dispose of spent nuclear fuel and DSRS. In boreholes for DSRS, cementitious materials are intended to be used as structural material, immobilization matrix and as backfill. The understanding of the performance of these materials is essential to ensure the safety of the facilities during their required lifetime, from centuries to many thousands of years, depending on the initial activity and half-life of the waste. This review approaches the behavior of the cement from the hydration and hardening to the long-term processes that can affect its durability. Three main causes of failure of repository-engineered barriers are recognized: a) the formation of a preferential pathway for the migration of the contained radionuclides to the biosphere; b) loss of resistance and cohesion of the structural cementitious material; and c) the increase in the corrosion processes of the metallic components of the structures that affect the overall containment of the facility.